Multicentral Retrospective Analysis of Venetoclax-Based Treatments in AML and MDS: A Real-World Study by the Turkish Hematology Network Group - Acar, Ibrahim Halil; Aslaner Ak, Muzeyyen; Akyol, Gulsah; Kars, Taha Ulutan; Ipek, Yildiz; Uysal, Ayse; Guvenc, Birol (Mdpi, 2024)
Background and Objectives: Acute myeloid leukemia and myelodysplastic syndrome are both clonal hematologic malignancies that primarily affect older adults. Current treatments for AML/MDS are both limited in number and efficacy. This study aims to evaluate venetoclax-based therapies in AML/MDS, focusing on overall survival and recurrence-free survival rates, and to expand real-world data on its use. Materials and Methods: Clinical and laboratory data on patients with AML/MDS aged 18 >= treated with venetoclax between January 2019 and July 2022 were included. Survival analysis was calculated based on the period from 2019 to December 2023. Results: A total of 161 AML and 40 patients with MDS were included. The median age was 63.53 +/- 15.30 years for AML and 70.12 +/- 10.21 years for MDS. In both groups, over 55% are male. A total of 77.6% of patients with AML and 75% of patients with MDS received treatment prior to venetoclax. Venetoclax was administered in combination with azacitidine to 84.5% of AML and 67.5% of MDS. The relapse rate in AML is approximately 15%. Overall, the 2-year survival rate is 46% and 18.73 months. The overall CR/CRi rate for patients with AML is 49.1%, while for patients with MDS, it is 50%. The 2-year survival rate for patients with MDS is 52.7%. The 2-year RFS rate was 75.5% for AML and 90.9% for MDS. The relapse rate in AML is approximately 15%. The percentage of adverse events leading to treatment discontinuation among those with grade 3-4 toxicity is low; 26.7% for AML (n = 43) and 15% for MDS (n = 6). Conclusions: Our real-world data demonstrate that venetoclax has the potential to improve overall survival rates when used in combination with HMAs and supports its use in patients with AML/MDS.
Keywords: acute myeloid leukemia; myelodysplastic syndrome; venetoclax; treatment outcome; malignancy